ANALISIS KUALITAS PELAYANAN PENGUJIAN KENDARAAN BERMOTOR DI KABUPATEN TEGAL (DI LIHAT DARI IKM) - Lailatul Istiqomah Dewi; Nina Widowati; Aloysius Rengga (Journal of Public Policy and Management Review, 2013)
The test vehicle is a vehicle assigned to address safety issues in the field of public transport safety concerns for users at both the regional and national level. This study aims to identify and menganilisis quality of services performed by the Department of Transportation, Communication and Information Tegal regency. Type used is descriptive qualitative, by using reference measurements on basis of the satisfaction indext KEP MENPAN No.63/7/2003 which consists of 14 elements "relevan", "valid" and "reliable". The result of the satisfaction index calculation for obtaning a yield of 74,08 or in the good category (B). To improve the quality of care testing of motor vehicles so much better, employee testing vehicles in Tegal regency should pay attention to the service user satisfaction by adding facilities and infrastructure, as well as providing strict sanctions or penalties for employees who absent during working hours or working days